2020
DOI: 10.1180/mgm.2020.90
|View full text |Cite
|
Sign up to set email alerts
|

Secondary lanthanide phosphate mineralisation in weathering profiles of I-, S- and A-type granites

Abstract: This is a 'preproof' accepted article for Mineralogical Magazine. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…Microorganisms also assist weathering via production of acids (Ullman et al 1996). However, lanthanides can precipitate as insoluble secondary lanthanide phosphates such as rhabdophane, as reported previously (Banfield and Eggleton 1989; Taunton, Welch, and Banfield 2000; Sanematsu, Kon, and Imai 2015; Voutsinos, Banfield, and Moreau 2021) and as shown here. They are not solubilized via soil-associated acids (Gausse et al 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Microorganisms also assist weathering via production of acids (Ullman et al 1996). However, lanthanides can precipitate as insoluble secondary lanthanide phosphates such as rhabdophane, as reported previously (Banfield and Eggleton 1989; Taunton, Welch, and Banfield 2000; Sanematsu, Kon, and Imai 2015; Voutsinos, Banfield, and Moreau 2021) and as shown here. They are not solubilized via soil-associated acids (Gausse et al 2016).…”
Section: Discussionsupporting
confidence: 89%
“…7 & Supplementary Table 4) that showed that total lanthanide concentrations peaked in the lightly weathered (RPR1 - density 2.1 g/cm 3 ) granite (427 ppm), where La concentrations were over five times higher than in fresh granite. The high enrichment of lanthanides in lightly weathered rock has been described previously (Banfield and Eggleton 1989; Voutsinos, Banfield, and Moreau 2021), and is attributed to redistribution of lanthanides from more weathered rock into phosphate phases at the weathering front.…”
Section: Resultssupporting
confidence: 67%
“…Secondary phosphate can readily form by interface precipitation with REEs on mineral surfaces (Patel et al 2017;Kashiwabara et al 2018). The formation of REE phosphates involves the dissolution of primary REE-bearing phosphate (e.g., xenotime, monazite, and apatite), and the precipitation of REE phosphate (Ichimura et al 2020;Voutsinos et al 2021). Common LREE-bearing secondary phosphate mineral phases in the weathering environment include churchite (Y(PO 4 )•2H 2 O), rhabdophane ((Ce, Y, La, etc.,)(PO 4 )•H 2 O), and florencite (CeAl 3 (PO 4 ) 2 (OH) 6 ).…”
Section: Occurrence Of Rare Earth Element Nano-particlesmentioning
confidence: 99%
“…In these resources, the lanthanides are most often in the form of the following natural mineral phases [3]: a) Carbonate minerals: Bastnaesite (Ce,La)(CO3)F; Parisite Ca(Ce,La)2(CO3)3F2; Synchysite Ca(Ce,La)(CO 3 ) 2 F and Cebaite Ba 3 Ce 2 (CO 3 ) 5 F 2 containing lanthanides [6][7][8]; and Breunerite (Mg,Fe,Sc)CO3 or Dolomite (Ca,Mg,Sc)CO3 (accompanying the silicate albite mineral phase) containing scandium [9]; Yttrium bonded to 25 carbonates compounds. b) Phosphate minerals: Lanthanides in calcium substituted in phosphates as fluoride, chloride or hydroxide) Ca5(PO4)3(F,Cl,OH): Polymetalic monazite; (Ce,La,Nd,Th)PO4: Aluminum phosphates florencite CeAl3(PO4)2(OH)6 containing lanthanides [10][11][12] and Scandium phosphate anhydrous and hydrous species, such as Pretulite (ScPO4) and Kolbeckite (ScPO4 2H2O) [13]; Yttrium phosphate minerals -Xenotime (YPO4) and also, other 9 phosphates, vanadates and arsenates [14]; c) Silicate minerals: Kainosite Ca2(Y,Ce)2Si4O12CO3H2O; Ritholite (Ce,Ca)5(SiO4,PO4)3(OH,F); Gadolinite (Ce,La,Nd,Y)2Fe 2+ Be2Si2O10; Allanite (Ce,Ca,Y)2(Al,Fe 3+ )3(SiO4)3OH, containing lanthanides and yttrium [15][16][17][18]; Scandium as an essential element in the following silicate minerals mono silicate Cascandite Ca(Sc,Fe 2+ )Si3O8(OH)), Cyclosilicate bazzite Be3(Sc,Al)2Si6O18, Disilicate thortveitite (Sc,Y)2Si2 O7), and Orthosilicate eringaite Ca3Sc2 (SiO4)3 [19]. d) Oxide minerals: Fergusonite (Ce,La,Nd)NbO 4 , Loparite (Ce,La,Na,Ca,Sr)(Ti,Nb)O 3 ; Euxenite (Y,Ca,Ce,U,Th)(Nb,Ta,Ti)2O6; Brannerite (U,Ca,Y,Ce)(Ti,Fe)2O6 containing lanthanide and yttrium.…”
Section: Introductionmentioning
confidence: 99%